Lightering operation on beach, Nome, August 1905 - Nowell, Frank H., 1864-1950 (1905)
Caption on image: Second day's work on Nome Harbor, Aug. 10th 1905. Cost of landing 103 piles, $42.00. Photo by F.H. Nowell, Aug. 12th 1905. 4125 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number